Development of a Web-Based Musculoskeletal Pain Management Information System - Olajide, Oluwole B; Nwosu, Ikechukwu; Sogunro, Samson Oluyemi (Discoveries in Agriculture and Food Sciences, 2016)
Musculoskeletal symptoms among adolescents are related to the time spent using a computer, but little is known about the seriousness of the symptoms or how much they affect everyday life. The purpose of the present study was to examine the intensity of musculoskeletal pain and level of inconvenience to everyday life, in relation to time spent using a computer. This paper developed a system that determines the likelihood of musculoskeletal pain and uses the data stored from the likelihood in developing a predictive model to re-evaluate future data; achieved by – identifying the risk factors and their relationship with the likelihood of musculoskeletal pain, design the system which will be used in the development and implement the design using java programming language. The methodology of the system involved the identification of the requirements and their relationship with the determination of musculoskeletal pain likelihood; the model involved the allocation of points to each label of the risk factors. Ranges of the sum of points are then used to determine the musculoskeletal pain of each user. The input risk factors’ data were collected from a number of participants as patients which were processed in determining their respective status (unlikely, likely, benign and malignant)-the data was later converted into an .arff file format. For the implementation, the software used in performing the detection was implemented in java using the Netbeans IDE 7.1 while the predictive models were implemented using the java API,– a java oriented; data mining tool used for performing classification and forecasting. At baseline a self-administered questionnaire was distributed to 853 participants from 46 different work sites (382 men and 471 women) who, at baseline, had been free from neck and upper extremity symptoms during the preceding month. Work-related exposures, individual factors, and symptoms from the neck and upper extremities were assessed. Observations of working technique were performed by ergonomists using an ergonomic checklist. Incidence data were collected asking for information on the occurrence of neck, shoulder and arm/hand symptoms. Perceived exertion was rated on a modified scale ranging from 0 (very, very light) to 14 (very, very strenuous). Perceived comfort was rated on a 9-point scale ranging from -4 (very, very poor) to +4 (very, very good) in relation to the chair, computer screen, keyboard, and computer mouse. It was also observed that correct alignment with the computer reduces all the musculoskeletal pain and thus corrects the computer users about the use of ergonomic sitting posture when using the computer. There was a strong association between high perceived exertion and the development of neck, shoulder, and arm/hand symptoms. Moreover, there was an association between poor perceived comfort and neck pain. Surveillance of computer users may include perceived exertion and comfort to target individuals at risk for neck and upper extremity symptoms.